Species Composition, Genetic Structure, and Pathogen Prevalence in Tick Populations in Guangxi, China - Na Jiang; Haoqiang Tian; Chunfu Li; Rui Ma; Mengyun Liu; Shurong Wang; Qingan Zhou; Xiankai Wei; Juanmei Mo; Zimei Chen; Zhaoan Sheng; Lei Duan; et al. (Zoonoses)
Ticks are important vectors for many pathogens affecting humans and animals. This study was aimed at investigating the species composition, genetic diversity, and potential transmission risks of tick-borne pathogens in the Guangxi Zhuang Autonomous Region, China. A total of 980 ticks were collected from 14 prefecture-level cities in Guangxi between March and July 2021. Ticks were identified morphologically and genetically, and the population diversity of Rhipicephalus microplus was analyzed according to 16S rDNA, COXI , and ITS-2 gene sequences. Population genetics was assessed through F ST , AMOVA, and phylogenetic analyses. PCR was used to detect five common tick-borne pathogens: Rickettsia , Babesia , Theileria , Borrelia burgdorferi , and Anaplasma phagocytophilum . Rhipicephalus microplus was the dominant tick species, and was observed in 92.04% of all samples. Genetic diversity analysis revealed higher haplotype diversity for the 16S rDNA and COXI genes than the ITS-2 gene; these findings suggested a faster evolutionary rate for the first two markers. Population genetic differentiation was observed between Rhipicephalus microplus populations in Guilin, Hechi, and other regions, probably because of geographic isolation. Pathogen analysis revealed a 13.27% overall infection rate, and identified three Rickettsia , two Babesia , and three Theileria species. Co-infection with Theileria and Rickettsia was also detected. Notably, neither Borrelia nor Anaplasma was found in the tick samples. Phylogenetic analyses confirmed the distinctiveness of the Rickettsia and Piroplasma groups. This study provides a comprehensive assessment of tick species diversity and tick-borne pathogens in Guangxi, highlighting the potential health risks posed by Rhipicephalus microplus . The findings emphasize the need for expanded tick surveillance, enhanced pathogen detection methods, and integrated management strategies to mitigate the spread of tick-borne diseases. Future research should include the collection of free questing ticks and metagenomic approaches to provide a more comprehensive understanding of pathogen risk in the region.